Sustainability and Role of Engineering Education: SERINA - Alfredo Soeiro (2019)
In the IACEE (International Association for Continuing Engineering Education - www.iacee.org) world conference of 2016 a declaration was signed by participants. IACEE is an international organization dedicated to the Continuing Professional Development (CPD) and to the Continuing Education in Engineering (CEE). This declaration resulted in the creation of SERINA (http://serina.iacee.org). SERINA means Sustainability Education and Research in Action. SERINA recognizes the scale and complexity of the gap between existing solutions and the needs facing our planet concerning sustainability. SERINA is likely placed to act on this opportunity. SERINA seeks to pivot the organization to connect individuals, universities, industry, government and NGO organizations to meet the grand challenges facing humanity and the world. Keeping with its dedication to lifelong learning, SERINA has developed and will continue to develop global initiatives to address those twenty-one century challenges threatening the survival of human kind through collaboration, design, creative thinking and engineering. SERINA wants to implement the Porto declaration within the engineering community and influence stakeholders to comply with a framework of global sustainable development. Change and improvement can be obtained mostly by education and training of the current engineering community around the world.